2016
DOI: 10.1371/journal.pone.0150333
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Caribou Movements: Seasonal Ranges and Migration Routes of the Central Arctic Herd

Abstract: Migration is an important component of the life history of many animals, but persistence of large-scale terrestrial migrations is being challenged by environmental changes that fragment habitats and create obstacles to animal movements. In northern Alaska, the Central Arctic herd (CAH) of barren-ground caribou (Rangifer tarandus granti) is known to migrate over large distances, but the herd’s seasonal distributions and migratory movements are not well documented. From 2003–2007, we used GPS radio-collars to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 57 publications
2
67
2
3
Order By: Relevance
“…Whereas monitoring data collected on the CAH in the early 1980s reported that calving grounds were located adjacent to the coast (Cameron et al ), our results mirrored patterns in more recent studies where calving grounds were located inland, south of the oil fields (Fig. ; Arthur and Del Vecchio , Nicholson et al ). Similar to the Teshekpuk and Porcupine caribou herds, caribou in the CAH selected for herbaceous mesic vegetation during the calving period (Fancy and Whitten , Wilson et al ), and reduced their selection for wetter vegetation types during the mosquito harassment period (Walsh et al , Parrett , Wilson et al ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Whereas monitoring data collected on the CAH in the early 1980s reported that calving grounds were located adjacent to the coast (Cameron et al ), our results mirrored patterns in more recent studies where calving grounds were located inland, south of the oil fields (Fig. ; Arthur and Del Vecchio , Nicholson et al ). Similar to the Teshekpuk and Porcupine caribou herds, caribou in the CAH selected for herbaceous mesic vegetation during the calving period (Fancy and Whitten , Wilson et al ), and reduced their selection for wetter vegetation types during the mosquito harassment period (Walsh et al , Parrett , Wilson et al ).…”
Section: Discussionsupporting
confidence: 85%
“…). We used a consistent area of availability to enable comparisons in resource selection across periods and because caribou are highly mobile and can easily travel within this area during early summer (Arthur and Del Vecchio , Nicholson et al ). We removed areas within the MCP that overlapped with the Arctic Ocean (bounding the north end of the study area).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of changing plant communities could be alleviated somewhat because Rangifer is known to be versatile in their feeding habits, and the diet composition of caribou and reindeer varies across the species' range (Bergerud 1974;Thompson and Barboza 2013). Nicholson et al (2016) suggested that the observed flexible use of winter ranges by caribou may be beneficial in a changing climate, allowing them to adjust range use in response to environmental conditions. Similarly, reindeer appear to be able to adjust behaviour and space use in response to icing events, and this provides some ability to minimize negative impacts of extreme weather (Stien et al 2010;Loe et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The energetic cost of locomotion of an animal is dependent on the characteristics of the surface over which they are travelling. Deep snow increases the energetic cost of locomotion and slows movement (Fancy and White 1987;Nicholson et al 2016), and caribou tend to select areas with lower snow depth for ease of movement and better access to forage (Duquette 1988;Johnson et al 2001). The migratory patterns of caribou are integral to their life history and show substantial flexibility in response to environmental conditions, particularly respecting snow conditions and temperature (Nicholson et al 2016;Le Corre et al 2017).…”
Section: Movement Migration and Distributionmentioning
confidence: 99%
“…The inventories from 2013, 2014, and 2015 represented the operation phase, except for the forestry activity in July 2013. It is generally believed that there is some random variation in habitat use by reindeer between years (Nicholson et al., ), which was also seen in the initial analysis of the data (Figure ); therefore, it makes sense to average the usage over a number of years to get stable estimate of the effects of the wind farm.…”
Section: Methodsmentioning
confidence: 98%